The Statistical Properties of Conversational Speech Level of Chinese People and the Check of Speech Level Moni-toring Systems - Bao Ziwei (Tongxin xuebao)
This paper offers some data concerning cenversational speech levels of Chinese such as （1） long term mean RMS values, （2） RMS values of four pitch tones of Chinese words, （3） peak values, and （4） RMS value in environment of different noise levels.Since conversational speech varies fast with time, and its level fluctuates within a wide range, the dynamic response of the monitor systems （VU meter, Sound Level Meter, as well as Level Recorder） have been tested in order to find a more suitable system for statistical measurement. The results suggest that the Level Recorder is preferable for this purpose.Based on measuring more than five thousand syllables, the statistical distribution of long term speech level have been determined. Moreover, the speech powers were calculated from the so called "Talker’s level" formula of Fletcher rather than from spherical wave, because of the scattering effect of head and torse must be taken into accournt.